A Comparative Study on Indonesian and Malaysian Consumers’ Perception and Preference Towards Handphones From China, South Korea, America, and Europe - Silvia Dewi Sagita Andik; Jono M Munandar; Mukhamad Najib (School of Business, IPB University (SB-IPB), 2018)
Most handphones in Indonesia and Malaysia are imported from other countries such as from America, Europe, China, and South Korea. The enhancement of global brands has reduced local brand preferences. This research aims to clarify the consumers’ perception towards brands of handphones in Indonesia and Malaysia by conducting comparative studies in both countries and examining the effects of product attributes and brand image on brand preference. Questionnaire surveys were conducted to 200 respondents from Indonesia & Malaysia. The data were analyzed by the descriptive analysis, Semantic Differential Scale Analysis, ANOVA test, and Structural Equation Modelling Partial Least Square (SEM-PLS). It has been clarified that there are differences in preferences between consumers in Indonesia and Malaysia in terms of product attributes. Thus, the results of this research give benefits to the market expansion and product development in both countries.Keywords: brand preference, consumers’ perception, country of origin, brand, structural equation modeling